The role of employer branding on attracting, developing and retaining talent: The case of a leading Portuguese business group - Sousa, Bianca (2018)
Employer branding has gained considerable attention from practitioners and academics on recent years. It is believed that corporate brand can only be fully implemented if it reaches all the stakeholders, not only consumers. Although there is substantial literature about how companies should build their brand as employers, little attention has been given to the concrete answers companies come up with when facing the challenge of building an employer brand. In this sense, this paper aims to reflect the role of Employer Branding to attract, develop and retain talent and aims to analyse the steps and answers that a leading Portuguese Business Group used to create their employer brand strategy. For reaching this goals, our reflection and analysis is essentially supported by the concepts of Internal Marketing, Corporate Branding, Employer Branding and Internal Branding. This research is a case study and has a qualitative and explorative nature, assuming particularly an action research methodology. The approach adopted was rigorous, following the stages of diagnosis (1st phase) and implementation (2nd phase) of an Employer Branding strategy in the Portuguese Business Group. As a result of this experience, the conclusions summarize a series of reflections necessary to implement an Employer Branding strategy in a real business scenario.